Ethical Issues in Schizophrenia Research: A Scoping Review and Qualitative Interview Study - Khairatun Hisan, Urfa (The Indonesian Institute of Science and Technology Research, 2024)
Schizophrenia is a major research focus due to its complex etiology and treatment challenges. Ethical issues in schizophrenia research include informed consent, decision-making capacity, and the protection of vulnerable populations. Not all schizophrenia patients can provide ethical consent, highlighting the need for careful consideration in research practices. This study examined empirical studies on these ethical domains, identifying significant gaps and offering recommendations. We aimed to synthesize ethical issues from the literature and understand ethics committee members' perspectives through a mixed-methods approach, including a scoping review and qualitative interviews with three ethics committee members. For the review, four major databases were systematically searched for studies related to ethical issues in schizophrenia research. As a result, 35 of 5,222 moderate and high-quality records were included in the scoping review. Eight themes emerged from the scoping review and interview process: informed consent and decision-making capacity; willingness to participate and compensation in research; risk-benefit consideration and perception; therapeutic misconception; participants safeguard; ethical issue in various study designs; research guidelines; and recommendations for the involved parties in schizophrenia research. We conclude that individuals with schizophrenia should actively participate in research decision-making, ensuring dignity and respect.